2014
DOI: 10.3389/fped.2014.00030
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Injury to the Neonatal Brain – What Can We Do?

Abstract: Perinatal brain damage is one of the leading causes of life long disability. This damage could be hypoxic–ischemic, inflammatory, or both. This mini-review discusses different interventions aiming at minimizing inflammatory processes in the neonatal brain, both before and after insult. Current options of anti-inflammatory measures for neonates remain quite limited. We describe current anti-inflammatory intervention strategies such as avoiding perinatal infection and inflammation, and reducing exposure to infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
1
8
2
Order By: Relevance
“…The results of this study revealed a strong correlation between caffeine treatment and the presence of OP. Despite caffeine’s effect on treating apnea of prematurity with favorable long-term outcomes [ 23 ], our study revealed a strong association between cumulative dosage and duration of treatment with caffeine and OP even when controlling for the effect of other risk factors. The results show that the adverse effect of caffeine is more evident in lower gestational age infants, which may be explained by the prolonged half-life of caffeine in their bodies due to diminished kidney abilities to eliminate the caffeine.…”
Section: Discussioncontrasting
confidence: 55%
“…The results of this study revealed a strong correlation between caffeine treatment and the presence of OP. Despite caffeine’s effect on treating apnea of prematurity with favorable long-term outcomes [ 23 ], our study revealed a strong association between cumulative dosage and duration of treatment with caffeine and OP even when controlling for the effect of other risk factors. The results show that the adverse effect of caffeine is more evident in lower gestational age infants, which may be explained by the prolonged half-life of caffeine in their bodies due to diminished kidney abilities to eliminate the caffeine.…”
Section: Discussioncontrasting
confidence: 55%
“…In spite of the caffeine effect on treating apnea of prematurity with favorable long-term outcomes (Ofek-Shlomai, & Berger, 2014), our study results revealed a strong association between caffeine dose and duration of treatment and OP in longitudinal data analysis even when controlling for the effect of gestational age and weight gain and other medications. It is well studied that caffeine causes calciuria and creates negative calcium balance in preterm infants.…”
Section: Is Caffiene a Risk For Op? 49contrasting
confidence: 72%
“…Many anti-inflammatory agents have been effective in the perinatal brain (reviewed in Ofek-Shlomai (Ofek-Shlomai and Berger, 2014). These have also been effective against inflammation associated with adult traumatic brain injury (Abdel Baki et al, 2010; Moro and Sutton, 2010) and tissue damage from lipopolysaccharide (Brothers et al, 2010).…”
Section: Strategies For Improving Protection and Repairmentioning
confidence: 99%